Penerapan smart environment pada Pemukiman Kumuh di Bantaran Kali Code Kota Yogyakarta - Dewi Nofita Sari (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
The purpose of this study was to determine the application of a smart environment in slums inBantaran Kali Code, Kota Yogyakarta. To be able to obtain these objectives, the research meth-od used is to use a descriptive approach through a literature study. The location of this researchis by the case studies that have been determined namely in the Bantaran Kali Code YogyakartaCity. The data used in this study are secondary. The results of this study are the application of asmart environment to create an environment that provides comfort for residents, providesbeauty for those who see it both physically and non-physically. Smart environment and able tochange settlements that were initially dirty and dirty into clean and attractive settlements. Theidea of coloring houses is a good idea.